Opening Business Freedom in Eastern Bloc Countries As Exampled by Poland - Jakub MROŻEK (Communications of International Proceedings, 2025)
This article describes the circumstances surrounding the enactment of the first act in the Eastern Bloc – the Polish act introducing freedom of business activity. Although the opening of freedom of business activity undoubtedly constituted a breakthrough in the economies of socialist countries, the available scholarly literature devotes surprisingly little attention to it, focusing instead on the events that followed – the fall of communism in Central and Eastern Europe. The few publications describing the opening of freedom of business activity also tend to overlook the political and economic context surrounding the enactment of these regulations. The article draws on literature from the turn of the 1980s and 1990s, as well as contemporary literature describing the then-current elements of the political and economic system of socialist Poland. Furthermore, it briefly characterizes the restrictions on business activity at the time, citing selected legal regulations in this area. The economic situation of the country in the late 1980s, including desperate attempts at economic reform, is then presented. The article then describes the most important changes introduced by the act introducing freedom of business activity. The final section describes the impact the adoption of these changes had on the economic transformation process in Poland. Furthermore, it is demonstrated that the process of decomposition of the Eastern Bloc began even before the so-called Autumn of Nations, and consequently, that the first changes were implemented by communist governments. JEL Classification: A12, B24, K20, K30, M10, M20
Keywords: Freedom of enterprise; economy; Eastern Bloc; socialism; free market; Poland